Trudności w ustaleniu etiologii zmian płucnych u 15-letniej dziewczynki z wrzodziejącym zapaleniem jelita grubego - Góra, Anna; Bąk-Drabik, Katarzyna; Porębska, Jolanta; Halkiewicz, Franciszek; Ziora, Katarzyna; Machura, Edyta (Pediatria Polska - Polish Journal of Paediatrics, 2017)
Ulcerative colitis (UC) is an inflammatory bowel disease. In the course of this disease, a number of extraintestinal manifestations have been described. They can occur in almost every organ and system, which allows to consider UC as a systemic disorder. Pulmonary manifestations are rare. Their clinical picture is diverse, often mimicking the separate disease entities of respiratory system. The symptoms presented by patients are non-specific. Diagnosis of pulmonary changes in patients with UC is difficult due to complex relationships between pulmonary diseases and inflammatory bowel diseases (IBD). Below we present a case of a 15-year-old patient with UC and pulmonary disease, in which finding the etiology of pulmonary changes was associated with many difficulies.